MEASURING INSTRUMENT FOR REFILLED DRINKING WATER USING A TDS SENSOR - Dudi Adi Firmansyah; Kamila Rofa Khairunnisa Ibadurrohman; Bernadus Bisma Titis Restu Aji; Suprijanto Suprijanto (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
Water is an essential need for humans and consumed as drinking water after fulfilling the health requirement in the Republic of Indonesia Minister of Health Regulation No.492/Menkes/Per/IV/2010. Due to the increasing demand, there are currently many refilled drinking water stores as an economical and practical alternative way to people. However, their safety still needs to be tested in the laboratory. This condition is impractical so that it needs a portable measuring instrument especially based on the TDS sensor that can measure the total dissolved solids (TDS) and electrical conductivity (EC) at once, which determines the taste and safety of the water. TDS sensor calibration at 80.5 to 966 ppm shows a 93.4% accuracy; 99.8% precision and 1.3 ppm hysteresis. In comparison, EC calibration at 161 to 1932 microsiemens/cm produces an average of 82.3% accuracy, 97.1% precision, and 1.0 microsiemens/cm hysteresis. This prototype is then employed to measure the water sample and determine its safety to consume and observed a decreasing trend of TDS and EC (194.1 ppm and 388.2 microsiemens/cm) as compared to the water spring sample (20.2 ppm and 402.3 microsiemens/cm). The prototype also has a Bluetooth module that enabling the remote observation on a cell phone without the presence of a telephone network.